Effect of changing window type and ventilation strategy on indoor thermal environment of existing garment factories in Bangladesh - Hossain, Md Mohataz; Lau, Benson; Wilson, Robin; Ford, Brian (2017)
This paper presents two workable solutions that can significantly improve the indoor thermal environment within workspaces in existing ready-made garment (RMG) factories in the tropical climatic context of Bangladesh. The research involved field studies in three multi-storey factory buildings, interviews with workers and owners and simulation studies. Field data indicated that the existing window configurations and limiting the ventilation strategy to occupied hours caused overheating of the indoor environment. Among a list of proposals, the building owners saw value in implementing two solutions (i.e. altering existing window type to one with a higher effective opening area and adopting a night-time ventilation strategy) in their existing buildings as well as proposed new buildings. To quantify the benefits, a validated simulation study was conducted. The findings confirm that these two interventions can provide reductions of up to 23% in overheated working hours and in so doing, improve workers’ thermal comfort and well-being.